Research on Legal Services and Poverty: Its Relevance to the Design of Legal Services Programs in Developing Countries - Clarence J. Dias (Washington University Law Quarterly, 1975)
Depending upon their design and implementation, legal service programs can certainly assist in the dissemination of knowledge of legal rules and rights among sections of the society that otherwise would not have such knowledge. Legal service programs can thus encourage the mobilization of law by providing the information without which individuals might not be able to assert their rights. These programs should also increase access of the poor to dispute settlement mechanisms and, to the extent the poor are helped to vindicate their legal rights, create a sense of the efficacy of seeking recourse through the legal system, thus altering the perceptions of the poor that the formal system of legal justice is biased against them.
Keywords: Legal research